Mechanistic Insights into the Synthesis of Telluride Colloidal Quantum Dots with Trioctylphosphine‐Tellurium. Issue 38 (13th October 2020) - Shuklov, Ivan A.; Mikhel, Igor S.; Nevidimov, Alexander V.; Birin, Kirill P.; Dubrovina, Natalia V.; Lizunova, Anna A.; Razumov, Vladimir F.
Abstract: The combined NMR and quantum chemical study of tellurium solution in trioctylphosphine, for the first time, revealed the new unexpected P−Te species. The observed intermediates are absolutely different from the species forming in the reaction of trialkylphosphines with chalcogens up in the group. This finding sheds new light on the mechanism of telluride nanocrystals formation and allow to rationalize the application of this key tellurium precursor in the synthesis of nanostructures. The studied solution was applied in the synthesis of HgTe colloidal quantum dots. Abstract : The solution of tellurium in trioctylphosphine (TOP) is a key precursor in the synthesis of telluride nanostructures. 125 Te and 31 P NMR spectroscopy was applied to study the solutions of Te in different Te:TOP ratios. Unknown P−Te species were identified. Next quantum‐chemical simulation of chalcogene‐trialkylphosphine adducts revealed the nature of unforeseen P−Te adducts. The studied solution was applied in the synthesis of HgTe nanocrystals.